Migratory phenomenon of Africans to Europe challenge of living together - Gabriel Gaston Tata (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The cohabitation in a multicultural society asks for an inter-subjectivity in terms of unity and specificity. It requires that the individual be recognized, and together become authentic partners of dialogue. In encountering others, some points of insertions may be needed but with the necessity to respect the principle of distinction, and to have an objective to look on the risk of separation or the one of confusion. Cultural diversity allows then the dialectic that will be shown in the training liberties by constructive dialogue. When diversity, an archetypal value of cohabitation breaks the challenges of the exclusivist "we" and the one of a bitter "they", it results in a cross-culturality, as long as self and other gratitude, and to an interior and exterior reconciliation. Living together in a world of a plurality of culture, is not an impoverishment, or a personal ruin, because every cultural identity can reveal itself and transform our life.